MICROFINANCE AND RURAL PROSPERITY: A STUDY ON LIVING STANDARD ENHANCEMENT - Arora, Gaurav; Sutariya, Jaimini (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Microfinance institutions (MFIs) have become effective instruments for advancing economic growth, poverty reduction, and financial inclusion. MFIs enable people, especially women, to launch companies, enhance their standard of living, and become financially independent by offering small loans and financial services to underprivileged populations. Financial services like loans, savings accounts, insurance, and training that are given to low-income people or groups without access to traditional banking services are referred to as microfinance. Many people believe it to be an effective instrument for reducing poverty. The foundation of microfinance was the belief that by providing credit and other financial assistance to the poor, they would be able to develop and start making a life, which would help them escape poverty. Microfinance is the most effective tool for the economic empowerment of rural inhabitants and a crucial element in the battle against poverty. The study makes an effort to examine how microfinance affects rural residents’ quality of life.